Understanding Javanese for Telkom University Students to Introduce Javanese to Non-Javanese Speakers - Pratama, Rifta Alifia Putra; Nugroho, Catur (eProceedings of Management, 2024)
Javanese is a widely spoken regional language in Indonesia. However, many people do not know Javanese and do notunderstand Javanese culture. Therefore, this research aims to understand the Javanese language and culture, as wellas provide an understanding of the Javanese language to students who do not know Javanese. This research will discussthe introduction of the Javanese language for students who do not know Javanese, especially Telkom Universitystudents. The data analysis used in this research is Miles and Huberman's interactive data analysis. The method usedin this research is qualitative method with a phenomenological approach. The purpose of this research is to find outthe meaning of the Javanese language by non-Javanese students at Telkom University. The research shows that incross-cultural communication between Javanese and non-Javanese students, the use of Javanese by non-Javanese islimited to the vocabulary mastered, and their understanding of Javanese focuses more on vocabulary than completesentences. Keywords-college students; cultural identity; intercultural communication; language communication.